2011
DOI: 10.3852/10-195
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of biotrophy in Hygrophoraceae inferred from combined stable isotope and phylogenetic analyses

Abstract: The nutritional modes of genera in Hygrophoraceae (Basidiomycota: Agaricales), apart from the ectomycorrhizal Hygrophorus and lichen-forming taxa, are uncertain. New δ(15)N and δ(13)C values were obtained from 15 taxa under Hygrophoraceae collected in central Massachusetts and combined with isotopic datasets from five prior studies including a further 12 species using a data standardization method to allow cross-site comparison. Based on these data, we inferred the probable nutritional modes for species of Hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 35 publications
5
54
0
3
Order By: Relevance
“…Moncalvo et al (2002) identified many phylogenetic clades that were later supported as belonging to the Hygrophoraceae by Lodge et al (2006), Matheny et al (2006), Lawrey et al (2009) and Binder et al (2010). Neither Binder et al (2010) nor Seitzman et al (2011) found support for a monophyletic family, but Matheny et al (2006) found Bayesian support for a monophyletic Hygrophoraceae s.l. if Camarophyllopsis and Neohygrophorus were excluded.…”
Section: Of the International Code Ofmentioning
confidence: 95%
See 2 more Smart Citations
“…Moncalvo et al (2002) identified many phylogenetic clades that were later supported as belonging to the Hygrophoraceae by Lodge et al (2006), Matheny et al (2006), Lawrey et al (2009) and Binder et al (2010). Neither Binder et al (2010) nor Seitzman et al (2011) found support for a monophyletic family, but Matheny et al (2006) found Bayesian support for a monophyletic Hygrophoraceae s.l. if Camarophyllopsis and Neohygrophorus were excluded.…”
Section: Of the International Code Ofmentioning
confidence: 95%
“…Matheny et al (2006) were first to show strong support for a monophyletic Hygrophoraceae. The Hygrophoraceae appears to be mostly biotrophic based on stable carbon and nitrogen isotope signatures, though only the type genus, Hygrophorus, forms ectomycorrhizal associations with tree roots (Seitzman et al 2011;Tedersoo et al 2010). Acantholichen, Cora, Corella, Cyphellostereum, Dictyonema, Lichenomphalia and Semiomphalina species form lichens with green algae or cyanobacteria Matheny et al 2006;Redhead et al 2002), Eonema is associated with live ferns and grasses , and Arrhenia and Cantharellula are generally associated with bryophytes ).…”
Section: Of the International Code Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their belowground ecology, in particular their nutritional mode(s), remains unclear despite recent attention by several researchers. Indirect evidence from carbon and nitrogen stable isotope ratios suggests that at least some taxa are biotrophic (Seitzman et al 2011), and further evidence of a mycorrhiza-like association with plants has been demonstrated recently (Halbwachs et al unpublished data).…”
Section: Introductionmentioning
confidence: 80%
“…Based on BLASTN results, sequences were selected according to the outcomes of recent phylogenetic studies on Agaricales Underw. (Matheny et al 2006;Binder et al 2010;Ovrebo et al 2011;Seitzman et al 2011). A combined analysis of ITS and LSU sequences was carried out with sequences from the same strain or specimen.…”
Section: Methodsmentioning
confidence: 99%